(untitled) (Research, Society and Development, 2023)
The life expectancy of the population has increased and improved over the years due to the quality of living conditions, housing and health. However, it is understandable that the elderly are susceptible to multiple diseases due to a variety of factors. It is known that due to the high prevalence of non-communicable chronic diseases, the use of drugs has increased significantly, accompanied by higher incidences of polypharmacy. Therefore, pharmaceutical care in elderly and polydrug populations is extremely important for monitoring, not only to promote the rational use of drugs, but also to provide better adherence to treatment and, consequently, better clinical and economic results. In this way, the present research is an integrative review to analyze evidence in the literature regarding the role of the clinical pharmacist in pharmaceutical care, as well as their interventions and the impacts caused on polymedicated elderly. For this, data collection was carried out from secondary sources, through a bibliographic survey in national and international databases. 834 articles were found, and only 20 studies were used for the present research. The results obtained in this study can demonstrate that the performance of pharmaceutical care and its intervention in geriatric and polymedicated patients can adjust doses, reduce drug interactions and reduce costs, in addition to improving the quality of life of these patients.